Subcarrier allocation in OFDMA systems: beyond water-filling - Kittipiyakul, S.; Javidi, T. (2004 38th Asilomar Conference on Signals, Systems and Computers, 2004)
This paper considers the issue of optimal subcarrier allocation in OFDMA. When including time-varying packet arrivals and channels, we show, via a counter example, that water-filling-based subcarrier allocation policies, contrary to conventional wisdom, fail to provide rate-stability for an otherwise stabilizable OFDMA system. We briefly discuss the long-run throughput optimality in OFDM as demonstrated in (S. Kittipiyakul et al., 2004). In particular under a simple channel model, we consider a nonidling policy which balances the queues and outperforms water-filling policies by achieving the minimum average delay. In this paper, we provide simple computation algorithms for implementing such policies and provide simulations for a numerical comparative study.